2023
DOI: 10.31219/osf.io/pzqkm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Lexical Content of High-Stakes National Exams in French, German, and Spanish in England

Abstract: Surprisingly little is known about the number and frequency of words that beginner-to-low intermediate 16-year-old learners of French, German, and Spanish are expected to know when taking high-stakes national exams in England. This study presents exploratory analyses of the lexical content of the listening and reading tests of these exams, a corpus totalling 116,645 running words. Specifically, it seeks to understand the number and frequency of words that (a) this demographic seems to be expected to know and (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Very little research, however, has examined the specific lexical demands of the GCSE exams. In our recent analysis (Dudley & Marsden, 2023), we observed extensive use of unpredictable, low(er) frequency, and likely unknown words in four sets of GCSE exams and suggested that this may be contributing to the perceived and actual difficulty of foreign languages.…”
Section: Modern Foreign Language Education In Englandmentioning
confidence: 85%
See 1 more Smart Citation
“…Very little research, however, has examined the specific lexical demands of the GCSE exams. In our recent analysis (Dudley & Marsden, 2023), we observed extensive use of unpredictable, low(er) frequency, and likely unknown words in four sets of GCSE exams and suggested that this may be contributing to the perceived and actual difficulty of foreign languages.…”
Section: Modern Foreign Language Education In Englandmentioning
confidence: 85%
“…This insufficient coverage could be a consequence of organizations not actively using their lists when creating the exams or the lists not containing a high enough proportion of high-frequency words, given that high-frequency words would normally represent over 80% of any written or spoken text (Dang & Webb, 2014;Nation, 2006b;Webb & Nation, 2017;Webb & Rodgers, 2009a, 2009b. Corroborating the latter explanation are Dudley and Marsden's (2023) findings that 44% of the flemmas used in the corpus of exams at foundation and 45% at higher are indeed low(er)-frequency (defined in that study as beyond the 2,000 most frequent words). Relatedly, it may be that the lower coverage observed in our study is in part due to the high proportion (49% at foundation and 52% at higher) of low(er)-frequency flemmas on the AQA lists (see Online Supporting Information B for more information).…”
Section: To What Extent Is Teaching From the Awarding Organizations' ...mentioning
confidence: 99%